Evaluation of glutaraldehyde test and amount of rumen content chlorine in cases of vagal indigestion (Hoflund syndrome) due to reticuloperitonitis traumatica - Gul, Yusuf; Issi, Mustafa (Univ Zagreb Vet Faculty, 2009)
This study is published in order to present the rumen content, amount of chlorine, and the results of glutaraldehyde test in cattle clinically diagnosed with vagal indigestion (Hoflund syndrome) due to reticuloperitonitis traumatica (RPT). The working material included an experimental group, and a control group. The experimental group was made up of 52 cows of different breeds admitted to our clinic for examination and diagnosed with vagal indigestion due to RPT, their ages ranging between 2-14. The control group was made tip of 10 cows of different breeds determined to be healthy in clinical examinations, their ages ranging between 2-8. In total, there were 62 cows. After all cattle in the two groups were clinically examined, a minimum of 100 ml of rumen content samples were taken using rumen sounder. Rumen content chlorine levels was determined according to the Schales-schales method. In order to carry out the glutaraldehyde test in the 25 animals in the experimental group and all the animals in the control group, blood with EDTA was taken from the v. jugularis of the animals. As for the clinical parameters of the animals in the experimental group and the control group; the difference between the arithmetic means of body temperature (38.90 +/- 0.55 and 38.68 +/- 0.15 degrees C, respectively), heart frequency (85.92 +/- 19.88 and 72.00 +/- 7.26 item/minute, respectively), and rumen movement (2.75 +/- 1.99 and 8.70 +/- 0.48 item/5 minutes, respectively) was at the significance level of P<0.001. and the difference between the arithmetic means of respiration frequency (29.11 +/- 9.94 and 24.80 +/- 1.68 item/minute, respectively) was at the significance level of P<0.01. In this study, it was observed that the average value Of glutaraldehyde test was (2.44 +/- 1.18 minutes) in the experimental group, and it was stated that the difference between the groups was P<0.001. In conclusion, it is considered that the detection of rumen content chlorine levels, which is the most important parameter in determining abomasal reflux syndrome cases, might be helpful, especially in the diagnosis of functional gastric stenosis, and that the glutaraldehyde test might be useful in detecting back functional stenosis cases due to RPT.
Keywords: Hoflund syndrome; vagal indigestion; reticuloperitonitis traumatica; rumen chlorine; glutaraldehyde